Impact of liposomal bupivacaine on subjective recovery quality after surgery: a meta-analysis of randomized controlled trials - Zhang, Longyi; Yang, Shun; Liu, Xianchun; Chen, Linlin; Zhou, Xuelei; Mao, Wei; Zhao, Li; Li, Linji; Xie, Ying (Frontiers in Medicine, 2025)
BackgroundThe quality of recovery (QoR) is a multidimensional concept used to evaluate the restoration of physical and psychological functions after surgery. It is a key measure for assessing surgical efficacy, anesthetic modalities, and the effectiveness of perioperative interventions. Liposomal bupivacaine (LB), a long-acting local anesthetic recently introduced, is characterized by its sustained-release profile and prolonged analgesic effect. However, empirical findings regarding the impact of LB on the quality of postoperative recovery remain inconclusive.MethodsOn 5 March 2025, we conducted a systematic search of the PubMed, Embase, Web of Science, Cochrane Library, Scopus, CNKI, and VIP databases to identify randomized controlled trials (RCTs) assessing the efficacy of LB in postoperative recovery. Eligible studies compared postoperative recovery outcomes between patients receiving LB and those in control groups who did not receive LB. The primary outcome of interest was the QoR score measured 72 h after surgery. Secondary outcomes included QoR scores at 24 and 48 h after surgery; pain scores at rest at 24, 48, and 72 h after surgery; incidence of postoperative nausea and vomiting (PONV); cumulative morphine-equivalent opioid consumption within 72 h after surgery; and patient satisfaction.ResultsThis meta-analysis included 11 RCTs comprising a total of 1,357 patients. The findings indicate that the LB group showed a statistically significant improvement in overall QoR scores 72 h after surgery [standardized mean difference (SMD): 0.52; 95% confidence interval (CI): 0.20, 0.85; P = 0.00]. Furthermore, LB use was associated with significantly reduced pain scores at 24, 48, and 72 h after surgery. The LB group also exhibited lower cumulative morphine-equivalent opioid consumption within 72 h after surgery, a reduced incidence of PONV, and significantly higher patient satisfaction scores.ConclusionThe use of LB was associated with improved QoR scores within 72 h after surgery, a reduced incidence of PONV, and decreased opioid consumption. These findings suggest that LB not only improves overall postoperative recovery but also mitigates associated adverse effects, thereby contributing to improved patient satisfaction and a more streamlined recovery trajectory. Nevertheless, further research is needed to assess its long-term efficacy and broader clinical applicability.Systematic review registration[https://www.crd.york.ac.uk/prospero/], identifier [CRD420251003585].